PENGGUNAAN BEBERAPA JENIS PERANGKAP DENGAN FEROMON TERHADAP KUMBANG KELAPA (Oryctes rhinoceros L.) (COLEOPTERA : SCARABAEIDAE) - Marco M. Supit; Dantje Tarore; Juliet M.E. Mamahit; James B. Kaligis (COCOS, 2014)
ABSTRACKCoconut plant (Cocos nucifera L) is a multifunction plant or a plant that has a high value of economy. In every part of the coconut plant can be use for every people needs because almost in every part of plant such as: the trunk, root, leafs and the fruits can be use for the everyday needs. Pest is one of the inhibitor factor in the production of coconut. The purpose of this research is to know the use some kind of traps with pheromone to the coconut beetle O. rhinoceros. This research is held in four different villages Kima Atas, Mapanget, Kayuwatu and Paniki, since last June until September 2013. This research use four different kinds of traps: trap A, trap B, trap C and trap D and in every inside trap there is a pheromone with the same dosage placed in four location were in every location there are four kinds of traps. The materials and the tools the we use in this research is sintetic pheromone for O. rhinoceros (ethyl-4-mathyloctanoata), four kinds of trap from Balit Palma, knife. machete, container, marker, label, camera and stationery. The result of this research shows that the largest amount of O. rhinoceros is found in trap B (126.0 insects),then trap C (30.0 insect), trap A (24.0 insects), and the lowest is found in trap D (15.0 insect), and base on the gender, female (111 insects) male (84 insect).Keywords: Coconut, O. rhinoceros, Pheromone, Trap